Alterity in Art: Towards a Theory and Practice of Infra-thin Critique. Issue 3 (November 2014) - Shilton, Siobhán
<x xml:space="preserve">Abstract</x> This article explores distinctively visual presentations and performances of alterity from the perspective of art theory and practice. It gives particular attention to Marcel Duchamp's notion and practice of the infra-mince. The 'infra-thin' is not usually related to postcolonial questions. However, numerous evocations of alterity in contemporary art, this article argues, resonate with Duchamp's infra-thin — not only in their practices but also in the ways in which they present the relationship between different cultures and views of 'difference'. Focusing on artwork responding to the 'Arab Springs' as a striking instance of wider aesthetics of resistance, this article shows how such art can be seen to adapt the infra-thin for the purposes of a multidirectional critique.